2005
DOI: 10.1002/jssc.200401863
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protoberberine alkaloids in several herbal drugs and related medicinal preparations by non-aqueous capillary electrophoresis

Abstract: A simple, rapid, reproducible, and universal non-aqueous capillary electrophoresis method has been developed for the separation and determination of three major active protoberberine alkaloids including berberine, palmatine, and jatrorrhizine within 7 min. The effects of the concentrations of acetic acid and electrolyte, the ratio of organic solvent, and the applied voltage on the separation were investigated. The optimum running buffer was composed of 50 mM ammonium acetate, 0.5% (v/v) acetic acid, and 10% (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 23 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…The respective detection limits of UPLC-PDA and UPLC-MS/MS techniques are in the range of 60-75 and 1.2-1.5 g L −1 for the three alkaloids, which are better than those reported using HPCE-UV. [12]. Both procedures allow the quantitation in the range studied although the quantification range for UPLC-PDA and UPLC-MS/MS were different.…”
Section: Linearity and Detection Limitmentioning
confidence: 97%
See 1 more Smart Citation
“…The respective detection limits of UPLC-PDA and UPLC-MS/MS techniques are in the range of 60-75 and 1.2-1.5 g L −1 for the three alkaloids, which are better than those reported using HPCE-UV. [12]. Both procedures allow the quantitation in the range studied although the quantification range for UPLC-PDA and UPLC-MS/MS were different.…”
Section: Linearity and Detection Limitmentioning
confidence: 97%
“…However, it is our believe that a more effective quality control practice for Huanglian should include the assay of a set of major alkaloids rather than a single species, and it is towards this objective that the present study was initiated. During the last decades, several methods have been reported for the determination of alkaloids in Rhizoma Coptidis extracts, and these methods included colorimetry [9], thin layer chromatography (TLC) [10], capillary electrophoresis [11][12][13], micellar electrokinetic chromatography [14], highperformance liquid chromatography (HPLC) with different detections including mass spectrometry [3,5,[15][16][17][18][19]. The colorimetric method determines only the total alkaloids content but is non-specific towards individual alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…The system is incompatible with online MS detection. Gao et al [21] reported that an MS compatible nonaqueous CE could be used to determine protoberberine alkaloids in several herbal drugs. In order to develop a CE-ESI-TOF-MS method for the analysis of alkaloids in R. coptidis, two CE-MS compatible BGEs -one aqueous and one nonaqueous system -were selected for optimization and performance evaluations.…”
Section: Optimization Of Ce Separation Conditionsmentioning
confidence: 99%
“…One publication [21] has reported that methanol and ACN containing ammonium acetate could be used to separate three protoberberine alkaloids in Chinese traditional herbs (R. coptidis, Cortex Berberidis, Cortex Phellodendri, etc.). Thus, in our study, a mixture of MeOH and ACN was chosen as the solvent medium, ammonium acetate was selected as electrolyte, and the nonaqueous BGE was optimized using both three alkaloid standards and real R. coptidis.…”
Section: Bge (I)mentioning
confidence: 99%
See 1 more Smart Citation